Poly-dipeptides encoded by the C9ORF72 repeats bind nucleoli, impede RNA biogenesis, and kill cells - Kwon, Ilmin (Science, 2014)
Many RNA regulatory proteins controlling pre-mRNA splicing contain serine:arginine (SR) repeats. Here we found that these SR domains bound hydrogel droplets composed of fibrous polymers of the low-complexity domain of heterogeneous ribonucleoprotein A2 (hnRNPA2). Hydrogel binding was reversed upon phosphorylation of the SR domain by CDC2-like kinases 1 and 2 (CLK1/2). Mutated variants of the SR domains changing serine to glycine (SR-to-GR variants) also bound to hnRNPA2 hydrogels, but were not affected by CLK1/2. When expressed in mammalian cells, these variants bound nucleoli. The translation products of the sense and antisense transcripts of the expansion repeats associated with the C9ORF72 gene altered in neurodegenerative disease encode GR(N) and PR(N) repeat polypeptides. Both peptides bound to hnRNPA2 hydrogels independent of CLK1/2 activity. When applied to cultured cells, both peptides entered cells, migrated to the nucleus, bound nucleoli, and poisoned RNA biogenesis, which caused cell death.